Regulation of myogenic tone and structure of parenchymal arterioles by hypertension and the mineralocorticoid receptor - Pires, Paulo W. (Am J Physiol Heart Circ Physiol, 2015)
Proper perfusion is vital for maintenance of neuronal homeostasis and brain function. Changes in the function and structure of cerebral parenchymal arterioles (PAs) could impair blood flow regulation and increase the risk of cerebrovascular diseases, including dementia and stroke. Hypertension alters the structure and function of large cerebral arteries, but its effects on PAs remain unknown. We hypothesized that hypertension increases myogenic tone and induces inward remodeling in PAs; we further proposed that antihypertensive therapy or mineralocorticoid receptor (MR) blockade would reverse the effects of hypertension. PAs from 18-wk-old stroke-prone spontaneously hypertensive rats (SHRSP) were isolated and cannulated in a pressure myograph. At 50-mmHg intraluminal pressure, PAs from SHRSP showed higher myogenic tone (%tone: 39.1 ± 1.9 vs. 28.7 ± 2.5%, P < 0.01) and smaller resting luminal diameter (34.7 ± 1.9 vs. 46.2 ± 2.4 μm, P < 0.01) than those from normotensive Wistar-Kyoto rats, through a mechanism that seems to require Ca(2+) influx through L-type voltage-gated Ca(2+) channels. PAs from SHRSP showed inward remodeling (luminal diameter at 60 mmHg: 55.2 ± 1.4 vs. 75.7 ± 5.1 μm, P < 0.01) and a paradoxical increase in distensibility and compliance. Treatment of SHRSP for 6 wk with antihypertensive therapy reduced PAs' myogenic tone, increased their resting luminal diameter, and prevented inward remodeling. In contrast, treatment of SHRSP for 6 wk with an MR antagonist did not reduce blood pressure or myogenic tone, but prevented inward remodeling. Thus, while hypertensive remodeling of PAs may involve the MR, myogenic tone seems to be independent of MR activity.